The Needs of English Culinary Booklet to Support Domestic and Foreign Promotion at the South Sumatra Culture and Tourism Office - Mona Monika; Rita Inderawati; Eryansyah Eryansyah (Makassar State University, 2022)
Abstract. This research aimed to determine the Domestic and Foreign Promotion at the South Sumatra Culture and Tourism Office needs in booklet development based on South Sumatra culinary. The data were obtained through the use of a questionnaire and semi-structured interviews. The sample of this study was stakeholders’ and staff at South Sumatera Culture and Tourism office. The data were analyzed both quantitatively and qualitatively. The needs analysis performed included TSA, deficiency analysis, PSA, and strategy analysis. The result of the need analysis showed that: 1) booklet material was important to support the region’s promotion. 2) developed English culinary booklet is important to help South Sumatra promote well because most of its employees already have an intermediate level of English. 3) Booklets that are remade only once a year with almost the same topic and only updated. 4) Integrating a culinary booklet was needed since there was only a booklet related to South Sumatera in general. 5) Integrating the Traditional Culinary Booklet of South Sumatra could encourage the awareness to learn traditional culinary of South Sumatra. 6) Most readers needed to learn the South Sumatera culinary booklet related to the main course, Dessert and Appetizer. 7) The readers prefer it will be using easy-to-understand language, and there is an explanation for difficult terms. Due to the needs, it was necessary to develop an English booklet by integrating South Sumatra culinary, which can support domestic and foreign promotion at the South Sumatra Culture and Tourism Office.Keywords: English Culinary Booklet, Tourism, Needs Analysis